Assessment tools for patients with stroke-related sarcopenia: a scoping review - Yanran Liang; Linli Xie; Wanwan Qiao; Runfang Guo; Hejia Wan; Jie Jing (Frontiers in Medicine, 2026)
Background The assessment of stroke-related sarcopenia (SRS) is not easy due to the paralysis and functional limitations in mobility after stroke. There is a need to identify tools for the assessment of SRS that stroke patients can complete. Objectives: This review aimed to summarize the tools that can be used to assess SRS. Methods Databases were systematically searched from the time of construction to 28 June 2026 based on the Arkensey and O’Malley framework. The databases searched included PubMed, Cumulative Index to Nursing and Allied Health Literature, Web of Science, Embase, Cochrane Library, China National Knowledge Infrastructure, Wanfang, VIP and China Biomedical Literature Database. Results This scoping review included 15 studies and identified 18 assessment tools, falling into four categories: 8 anthropometric tools, 7 performance-based test tools, 1 questionnaire, and 2 calculation formulas. ALM/SMI is the gold standard for muscle mass; TMT enables early screening via routine CT/MRI with no extra burden. HGS is preferred for muscle strength. CC and SARC-F suit large-scale initial screening. The validated ALM prediction formula provides an alternative when instrumental measurement is unavailable. Conclusion The results of our study can help healthcare professionals to rationally select the appropriate and optimal SRS assessment tools according to the actual situation.